Impact of the Bird-Beak Configuration on Postoperative Outcome After Thoracic Endovascular Aortic Repair: A Meta-analysis. (December 2019) - Marrocco-Trischitta, Massimiliano M.; Spampinato, Benedetta; Mazzeo, Girolomina; Mazzaccaro, Daniela; Milani, Valentina; Alaidroos, Moad; Ambrogi, Federico; Nano, Giovanni
Purpose: To investigate the association between the bird-beak configuration (BBC), a wedge-shaped gap between the undersurface of a thoracic endograft and the lesser curvature of the arch after thoracic endovascular aortic repair (TEVAR), and postoperative outcome after TEVAR.Methods: The study was performed according to the PRISMA guidelines. The PubMed, EMBASE, and Cochrane databases were searched to identify all case series reporting BBC after TEVAR between 2006 and April 2018. Data analysis was performed considering the difference in the risk of complications for presence vs absence of BBC. After screening 1633 articles, 21 studies were identified that matched the selection criteria; 12 of these reported detailed information to investigate the postoperative outcome using proportion meta-analysis with a random effects model. The pooled risk difference is reported with the 95% confidence interval (CI). Heterogeneity of the included studies was assessed with the I 2 statistic (low 25%, medium 50%, high 75%).Results: Complications occurred within a range of 0 to 72 months in 14.7% (95% CI 7.4% to 27.3%) of patients with BBC and in 6.3% (95% CI 2.5% to 15.4%) of patients without BBC. A cumulative incidence could not be assessed. The summary risk difference was 11.1% (95% CI −0.1% to 22.3%, p=0.052). There was significant heterogeneity ( I 2 =85.6%). The Egger test did not show evidence of publication bias (p=0.975). When specifically considering type Ia endoleak and endograft migration, the risk difference between BBC and non-BBC patients was 8.2% (95% CI 0.3% to 16.1%, p=0.042; I 2 =69.0%). The specific risk difference for endograft collapse/infolding and thrombosis was 3.7% (95% CI −3.5% to 11.1%, p=0.308; I 2 =10.2%).Conclusion: At present the literature does not provide statistical evidence to establish an overall prognostic value of the BBC. Nevertheless, the BBC appears to be associated with a high risk of type Ia endoleak and endograft migration, which warrants specific and long-term surveillance. Clinically relevant values for BBC grading should be established to perhaps define indications for preemptive treatment based on the presence of BBC only.